Ion‐scale secondary flux ropes generated by magnetopause reconnection as resolved by MMS - J. P. Eastwood; T. D. Phan; P. A. Cassak; D. J. Gershman; C. Haggerty; K. Malakit; M. A. Shay; R. Mistry; M. Øieroset; C. T. Russell; J. A. Slavin; M. R. Argall; et al. (Geophysical Research Letters)
Abstract New Magnetospheric Multiscale (MMS) observations of small‐scale (~7 ion inertial length radius) flux transfer events (FTEs) at the dayside magnetopause are reported. The 10 km MMS tetrahedron size enables their structure and properties to be calculated using a variety of multispacecraft techniques, allowing them to be identified as flux ropes, whose flux content is small (~22 kWb). The current density, calculated using plasma and magnetic field measurements independently, is found to be filamentary. Intercomparison of the plasma moments with electric and magnetic field measurements reveals structured non‐frozen‐in ion behavior. The data are further compared with a particle‐in‐cell simulation. It is concluded that these small‐scale flux ropes, which are not seen to be growing, represent a distinct class of FTE which is generated on the magnetopause by secondary reconnection.